Analisis Efektivitas Revitalisasi Pasar Tradisional dan Dampaknya Terhadap Pengelolaan Pasar, Jumlah Pengunjung dan Pendapatan Pedagang - Juliarta, Made Guna; Darsana, Ida Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 1, Januari 2016 (pp. 1 - 215), 2016)
In the process, the traditional markets are now becoming obsolete because of the assumption that the traditional market rundown, dirty and uncomfortable cause economic transactions in the traditional markets began to quiet. The realization of the Program for Revitalization of Traditional Markets considered necessary in order to excite the economy and the competitiveness of traditional markets amid the onslaught of the modern market. This research was conducted in Nyanggelan Market Pakraman Panjer which includes traders who sell a variety of merchandise. The object of this study was the effectiveness of the program Revitalization of Traditional Markets, income traders, market management, and the number of visitors. The sample consisted of 65 189 respondents of the total population by accidental sampling method. This research method using questionnaires, observation, and in-depth interviews. With descriptive analysis techniques and Wilcoxon tests obtained results of research that shows that the traditional market revitalization program in the Market Village Nyanggela Panjer classified as very effective in the amount of 89.89 percent and a positive impact on the management of the market, the number of visitors and revenue trader.
Keywords: Traditional Market Revitalization Program Effectiveness; Revenue; Total Visitors; Market Management